2009
DOI: 10.1063/1.3068192
|View full text |Cite
|
Sign up to set email alerts
|

Formation of planar defects over GeSi islands in Si capping layer grown at low temperature

Abstract: Coherently strained GeSi/Si(001) islands were overgrown with a Si capping layer of different thicknesses at temperature 300 °C. The structures of the islands and the Si capping layer were investigated by high resolution transmission electron microscopy. The shapes of the embedded islands were well preserved, whereas planar defects were observed exactly over the islands in the capping layers. The strain energy in regions over the islands accumulated with increasing thickness of the Si capping layer, resulting i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 21 publications
1
9
0
Order By: Relevance
“…This system allows us to examine the roles of both inhomogeneous strain and local island faceting on the epitaxial breakdown process. A similar study was recently reported where Si overgrowth was carried out at higher temperatures than used here, resulting in larger breakdown thicknesses 17 . That work attributed breakdown to fault generation on {111} through strain-induced partial dislocation introduction.…”
Section: Introductionsupporting
confidence: 84%
“…This system allows us to examine the roles of both inhomogeneous strain and local island faceting on the epitaxial breakdown process. A similar study was recently reported where Si overgrowth was carried out at higher temperatures than used here, resulting in larger breakdown thicknesses 17 . That work attributed breakdown to fault generation on {111} through strain-induced partial dislocation introduction.…”
Section: Introductionsupporting
confidence: 84%
“…The strain energy gradient in the compressive region is much larger than that in tensile region [5], so the Si migration is faster at the rim than at the central part over the QDs. The migration processes for the Si atoms at the rim and at the central part may be distinguished as fast migration and slow migration, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Compared with the work of Deng and Krishnamurthy [12], in which the nanopits are induced by carbon impurities, the remarkable advantage of the present work over theirs is that in the present growth process no other elements are involved, except Si and Ge. However, planar defects or stacking faults are formed in the capping layer in our case because the thickness of capping layer is larger than 20 nm, a critical thickness to generate stacking faults [5]. If the thickness of the capping layer is less than 20 nm, it is possible to grow defect-free QD molecules.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations